2022
DOI: 10.1038/s41420-021-00808-2
|View full text |Cite
|
Sign up to set email alerts
|

METTL14 promotes apoptosis of spinal cord neurons by inducing EEF1A2 m6A methylation in spinal cord injury

Abstract: Spinal cord injury (SCI) is a devastating traumatic condition. METTL14-mediated m6A modification is associated with SCI. This study was intended to investigate the functional mechanism of RNA methyltransferase METTL14 in spinal cord neuron apoptosis during SCI. The SCI rat model was established, followed by evaluation of pathological conditions, apoptosis, and viability of spinal cord neurons. The neuronal function of primary cultured spinal motoneurons of rats was assessed after hypoxia/reoxygenation treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…These findings indicate that METTL14 is involved in the regulation of axons after SCI (Wang et al, 2021). And another study found that METTL14 catalyzes the m6A methylation of EEF1A2 mRNA (Gao et al, 2022). Knockdown of mettl14 can increase the level of EEF1A2, and the opposite occurs after mettl14 overexpression (Gao et al, 2022).…”
Section: N6-methyladenosine Modification and Axonal Regeneration Afte...mentioning
confidence: 90%
See 4 more Smart Citations
“…These findings indicate that METTL14 is involved in the regulation of axons after SCI (Wang et al, 2021). And another study found that METTL14 catalyzes the m6A methylation of EEF1A2 mRNA (Gao et al, 2022). Knockdown of mettl14 can increase the level of EEF1A2, and the opposite occurs after mettl14 overexpression (Gao et al, 2022).…”
Section: N6-methyladenosine Modification and Axonal Regeneration Afte...mentioning
confidence: 90%
“…More importantly, further experiments also showed that overexpression of Mettl14 can induce apoptosis in vitro, as Mettl14 can promote the conversion of pri-miR-375 to miR-375, which is related to apoptosis and inhibits neural recovery (Wang et al, 2021). In addition, increased expression of METTL14 during SCI mediates the m6A modification of EEF1A2, which accelerates neuronal degeneration through the apoptotic pathway and impairs recovery after injury (Gao et al, 2022). EEF1A2 expression is reduced after SCI, while silencing of mettl14 increases EEF1A2 levels, decreases inflammatory cytokine production, and reduces neuronal degeneration in the spinal cord (Gao et al, 2022).…”
Section: N6-methyladenosine Modification and Cell Death After Spinal ...mentioning
confidence: 97%
See 3 more Smart Citations